(untitled) (Revista Iberoamericana de Bioética, 2022)
As migrant populations present increasingly complex health situations, strategies currently used Uruguay’s do not allow for the efficient management of interdisciplinary care and resolution of cases. The objective of this study is to identify interdisciplinary strategies that would optimize healthcare in the migrant community by closely examining the resolution of a complex case and analyzing the roles and relationships between the providers and professionals involved. In conclusion, the most effective strategies were building formal inter-institutional and inter-professional links and case management strategies. Moving forward, the development and implementation of standardized tools and the sharing of successful interdisciplinary experiences are suggested.